Community justice centres : new trajectories in law - Murray, Sarah (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book examines the phenomenon of Community Justice Centres and their potential to transform the justice landscape by tackling the underlying causes of crime. Marred by recidivism, addiction, family violence, overflowing courtrooms, crippling prison spending and extreme rates of incarceration, the criminal justice system is in crisis. Community Justice Centres seek to combat this by tackling the underlying causes of crime in a particular neighbourhood and working with local people to redesign the experience of justice and enhance the notion of community. A Community Justice Centre houses a court which works with an interdisciplinary team to address the causes of criminality such as drug addiction, cognitive impairment, mental illness, poverty, abuse and intergenerational trauma. The community thus becomes a key agent of change, partnering with the Centre to tackle local issues and improve safety and community cohesion. This book, based on research into this innovative justice model, examines case studies from around the world, the challenges presented by the model and the potential for bringing its learnings into the mainstream. This book will appeal to academics in law and criminology as well as psychology; it will also be of considerable interest to people working in the criminal justice system, including the police, government policy advisers, psychologists and social workers.
"Routledge focus"
"GlassHouse book"
OCLC-licensed vendor bibliographic record.
Keywords: Neighborhood justice centers; Community organization; Community-based corrections; Community policing; LAW / General; LAW / Alternative Dispute Resolution; LAW / Criminal Law / General